Airway Management for Trauma Patients. (5th September 2018) - Walrath, Benjamin D; Harper, Stephen; Barnard, Ed; Tobin, Joshua M; Drew, Brendon; Cunningham, Cord; Kharod, Chetan; Spradling, James; Stone, Craig; Martin, Matthew
Abstract: Trauma airway management is a critical skill for medical providers supporting combat casualties since it is an integral component of damage control resuscitation and surgery. This clinical practice guideline presents methods for optimizing the airway management of patients with traumatic injury in the operational medical treatment facility environment. The guidelines represent the knowledge and experience of 10 co-authors from 3 allied countries representing Emergency Medicine, Surgery and Anesthesia.